Method for testing blue light aging of OBA black anti-dazzle film

By attaching the OBA black anti-glare film (AG film) to the glass and performing irradiation test on the blue light test lamp board, the time-consuming and labor-intensive problem of existing blue light aging testing methods is solved, and fast and accurate blue light aging detection is achieved, which is suitable for the quality control of Mini-LED direct display modules.

CN119804290APending Publication Date: 2025-04-11NINGBO EXCITON TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411972593.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing OBA black anti-glare film (AG film) blue light aging testing methods are time-consuming and laborious, and cannot effectively detect blue light aging problems, affecting the display performance and appearance quality of the direct display module.

Method used

Provide a blue-ray aging test method that simulates real use scenarios. By attaching OBA black anti-glare film (AG film) to glass and placing it on the blue-ray test lamp beads for irradiation test, simplifying operation and greatly shortening the test duration.

Benefits of technology

This method can quickly and accurately detect the blue light aging of OBA black anti-glare film (AG film), simulate the real state of Mini-LED display modules that have been lit for thousands or even tens of thousands of hours, saving test time and improving testing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219781140000081
    Figure BDA0005219781140000081
  • Figure BDA0005219781140000091
    Figure BDA0005219781140000091
  • Figure HDA0005219781150000011
    Figure HDA0005219781150000011
Patent Text Reader

Abstract

A method for testing blue light aging of an OBA black anti-dazzle film is characterized in that the black anti-dazzle film (AG film) is attached to glass, and then the glass is placed on a lamp bead of a blue light test lamp panel for irradiation. The blue light aging method is easy to operate and short in operation time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of Mini LED backlight display screens, and specifically to a testing method for high-intensity blue light aging of an OBA black anti-glare film (AG film). Background Art

[0002] OBA (Optical Black Adhesive) is a surface encapsulation film used for Mini-LED direct display modules to improve the module's appearance ink color consistency, optical performance and surface protection film performance. It has anti-glare, good adhesion, and step filling properties. The excellent properties of OBA black anti-glare film (AG film) make it an indispensable key material in the packaging of Mini-LED direct display modules, and are of vital importance to improving the optical and durability of direct display modules. In addition, OBA black anti-glare film (AG film) also brings better appearance performance to Mini-LED direct display modules, and dilutes the large number of horizontal and vertical appearance seams generated when Mini-LED light panels are spliced. In the context of the rapid development and iteration of the Mini LED market, the innovation and optimization of OBA black anti-glare film (AG film) will continue to promote the progress of direct display modules.

[0003] During the use of Mini-LED backlight display screens, the blue light fading problem of OBA black anti-glare film (AG film) is a common quality problem, which will affect the display performance, appearance and long-term stability of the direct display module. The high-intensity blue light aging test of OBA black anti-glare film (AG film) is a necessary and particularly important link in the production process of direct display modules. By testing the blue light aging problem, the defects of OBA black anti-glare film (AG film) can be effectively detected, problems can be found in advance and the formula can be optimized, so as to ensure that the display performance of the direct display module reaches the expected design level. The high-intensity blue light aging test can evaluate the quality of OBA black anti-glare film (AG film) to ensure that its display performance in the direct display module meets the standard, thereby extending the service life of the direct display module, and ensuring that the appearance quality of the direct display module meets the market standards, thereby improving the market competitiveness of the product. Direct display modules with high ink color consistency are often favored by high-end consumers and promote the growth of sales and market share. The preliminary detection of OBA black anti-glare film (AG film) as a quality control link in the production of direct display modules can ensure product quality consistency and reduce losses caused by quality problems. In addition, these tests help evaluate the long-term stability and durability of the OBA black anti-glare film (AG film), ensuring that the transmittance of the OBA black anti-glare film (AG film) remains stable and normal during long-term use, meeting long-term use requirements and improving product qualification rate and market acceptance.

[0004] At present, Mini-LED display module manufacturers have no clear standards and industry specifications for the blue light fading test of OBA black anti-glare film (AG film). The main testing and certification standard is the 240-hour lighting result of the module light box by the display module manufacturer. This method cannot provide a reference for Mini-LED display modules that are lit for thousands or even tens of thousands of hours.

[0005] CN201721088231.8 discloses a power-on aging detection device for a liquid crystal dimming film, comprising a rectangular main frame, a plurality of rectangular plates are arranged in the transverse direction of the main frame for placing the dimming film, which slides in the transverse direction through a guide rail mechanism, a wire is arranged on the rectangular plate, one end of the wire is connected to the dimming film, and the other end is connected to the power supply through a time relay; a moving frame is arranged on one side of the main frame, a plurality of angle irons are arranged in the transverse direction of the moving frame, and the moving frame moves through a transverse guide rail. The utility model places the dimming film on the rectangular plate, connects the dimming film electrodes with wires, and forms a loop between the electrodes, the time relay and the power supply.

[0006] CN202121196183.0 discloses a power-on aging detection device for a liquid crystal dimming film, comprising a detection platform; a guide wheel is provided on the top of the detection platform, and a support frame is movably provided at the lower end of the detection platform, and the support frame comprises a left and right slide frame slidably connected to each other; a support seat 1 and a support seat 2 are movably provided at both ends of the detection platform, the support seat 1 is slidably connected to the left slide frame, and the support seat 2 is slidably connected to the right slide frame; an open groove is provided at one end of the support seat 1 and the support seat 2 close to the detection platform, and rollers are evenly spaced at the lower ends of the open grooves.

[0007] Existing detection methods are not well integrated with actual application scenarios when studying blue light aging performance. For example, in the field of electronic products, blue light aging has an impact on display screens, internal circuits and other components, but existing detection methods may only study some basic materials under laboratory conditions, without considering the actual performance of blue light aging performance in the complex internal environment of electronic products and how to effectively protect and detect it. This makes it difficult to directly apply the research results of these literatures to actual blue light aging performance testing work.

[0008] Therefore, a method for significantly shortening the time required to detect the blue light aging performance of an OBA black anti-glare film (AG film) is needed. The present invention provides a low-cost and easy-to-operate test method for detecting the blue light aging performance of an OBA black anti-glare film (AG film). Summary of the invention

[0009] In order to solve the problems that the existing OBA black anti-glare film (AG film) blue light aging test method is time-consuming and laborious, the present invention provides a method for accelerating the blue light aging test when simulating a real use scenario. The blue light aging method is easy to operate and has a short operation time.

[0010] Blue light fading of OBA black anti-glare film (AG film) refers to the color fading phenomenon of the color paste or masterbatch inside the OBA black anti-glare film (AG film) under long-term blue light exposure. This usually causes color changes on the appearance of the display module, affecting the beauty and market acceptance of the module light box, and at the same time causes the transmittance of the black anti-glare film (AG film) to increase, affecting the consistency of the module ink color in the dark state and the uniform distribution of brightness in the bright state.

[0011] The blue light aging test method of the OBA black anti-glare film (AG film) provided by the present invention is a test method in which the black anti-glare film (AG film) is attached to the glass and then placed on the lamp beads of a blue light test lamp board for irradiation.

[0012] In order to solve the technical problems of fading and increased transmittance caused by blue light aging, the present invention first provides a method for testing blue light aging of a film, comprising the following steps:

[0013] Step (1), sampling: selecting a film to be tested and glass with a light transmittance of more than 90%;

[0014] Step (2), sample preparation: remove the release film of the film to be tested, attach it to the front surface of the glass, and place the back of the glass on the blue light board to ensure that the glass and the lamp beads of the blue light board are in contact;

[0015] Step (3), aging test: Turn on the power of the blue light panel and perform an aging test;

[0016] Step (4), result calculation: After the test is completed, tear off the film to be tested, observe the fading, and calculate the transmittance change value.

[0017] Furthermore, the film to be tested is an OBA black anti-glare film (AG film), an OBA black adhesive layer anti-glare film (AG film), an OBA white diffusion adhesive (diffusion adhesive), etc.

[0018] Furthermore, the OBA black anti-glare film (AG film) is a kind of diffusion or transparent OCA adhesive layer and a black anti-glare film (AG film) laminated together.

[0019] Furthermore, the film to be tested is a transparent PET black anti-glare film (AG film) or a body black PET anti-glare film (AG film).

[0020] Furthermore, the transmittance of the OBA black anti-glare film (AG film) without a release film ranges from 20% to 55%.

[0021] Furthermore, the size of the membrane to be tested is O (mm)×P (mm), and the range of O and P is 50-500, or 100, 150, 200, 250, 300, 350, 400.

[0022] Furthermore, the glass is ultra-white glass.

[0023] Furthermore, the ultra-white glass is ultra-transparent low-iron glass with a light transmittance of more than 91%, or 95% or 98%.

[0024] Furthermore, the glass has a thickness of 2-10 mm, or 4 mm, 6 mm, 8 mm, and a smooth surface.

[0025] Furthermore, the size of the glass is M (mm)×N (mm), and the range of M and N is 100-800, or 200, 300, 400, 500, 600, 700.

[0026] Furthermore, the lamp board is a blue light lamp bead lamp board with a size of M (mm) × N (mm), and the range of M and N is 100-800, or 200, 300, 400, 500, 600, 700.

[0027] Furthermore, the number of lamp beads in the blue light lamp bead lamp board is 100-200, or 120, 150, or 180.

[0028] Furthermore, the OBA black anti-glare film (AG film) and the glass are in a pressure-free rolling attachment state.

[0029] Furthermore, during the aging test, the blue light aging process requires regular adjustment of the voltage and current of the voltage-stabilized power supply to maintain a total power of 100-200W, or 120W, 150W, 160W, 180W, and a single lamp bead power of 0.5W-3W, or 1W, 1.5W, 2.0W, 2.5W.

[0030] Furthermore, the aging test time is 10-30h, or 15h, 20h, 24h, 26h, 28h.

[0031] Furthermore, the transmittance is tested by a transmittance haze meter.

[0032] Further, specifically, the present invention provides a testing method, the method comprising the following steps:

[0033] (1) Take a piece of OBA black anti-glare film (AG film) with a size of 181mm×162mm, a piece of ultra-white glass with a size of 300mm×500mm and a transmittance of more than 91%, a blue light board with a size of 300mm×500mm and a total number of 150 lamp beads that can be lit normally, an AC-to-DC stabilized power supply, and an NDH7000 transmittance haze meter.

[0034] (2) Take a piece of OBA black anti-glare film (AG film) with a size of 181 mm × 162 mm, tear off the release film on the back, and gently roll the OBA black anti-glare film (AG film) onto a clean and uncontaminated glass. Place the back of the ultra-white glass with the black anti-glare film (AG film) on the blue light board, and ensure that the ultra-white glass and the lamp beads are all in contact. Use a regulated power supply to light up the blue light board, adjust the current and voltage to set the total power of the blue light board to 150 W and the power of a single lamp bead to 1 W. Figure 2 shown.

[0035] (3) Aging test. From top to bottom, stack the OBA black anti-glare film (AG film), ultra-white glass, and blue light aging light board in this order, and fix the glass in a certain position on the blue light board. After connecting the light board to the stabilized power supply, connect the circuit and the stabilized power supply, and turn on the stabilized power supply switch to start the test.

[0036] (4) Observation. After the 24-hour blue light aging test, turn off the voltage regulator, wait until the temperature of the light board and the glass drops to room temperature, tear off the black anti-glare film (AG film), and then observe the fading of the black anti-glare film (AG film). Use the NDH7000 transmittance haze meter to test its transmittance change.

[0037] The purpose of the present invention is to provide a test method that is easy to operate and can truly and quickly simulate the blue light aging of OBA black anti-glare film (AG film) on a blue light board, filling the gap in the blue light aging test of OBA black anti-glare film (AG film) for Mini-LED direct display modules.

[0038] The OBA black anti-glare film (AG film) high-intensity blue light aging test method provided by the present invention has the following advantages:

[0039] (1) The present invention provides a high-intensity blue light aging test method for OBA black anti-glare film (AG film). This method saves more testing time than the current method in which Mini LED backlight manufacturers on the market use module light boxes to illuminate the OBA black anti-glare film (AG film) for simulation, has a shorter development cycle, and can produce test results more quickly. The test results can simulate the real state of the Mini-LED display module OBA black anti-glare film (AG film) that has been lit for thousands or even tens of thousands of hours.

[0040] (2) The blue light aging test method adopted by the present invention is easy to operate in the actual production test process, does not require module light boards and light boxes, uses simple instruments, and has a wide range of test product series, including not only existing COB light board products, but also more advanced COG series products that are difficult to obtain and cannot be tested. COB (Chip On Bord) is a Micro / Mini LED packaging solution with integrated bracket-free packaging technology for multiple lamp beads on a PCB substrate, such as the 135-inch mass-produced COB light box of Zhaochi Crystal Display; COG (Chip On Glass) is a Micro / Mini LED packaging solution with integrated bracket-free packaging technology for multiple lamp beads on a glass substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of OBA black anti-glare film (AG film) attached to glass.

[0042] Among them, 1: OBA black AG film, 2: ultra-white glass.

[0043] Figure 2 Schematic diagram of the blue light aging test of OBA black anti-glare film (AG film).

[0044] Among them, 3: OBA black AG film, 4: ultra-white glass, 5: blue light board. DETAILED DESCRIPTION

[0045] In order to make it easier to understand the structure of the present invention and the functional features and advantages that can be achieved, the following will be combined with the preferred embodiments of the present invention and described in detail as follows:

[0046] like Figure 2 As shown, the OBA black anti-glare film (AG film) is on the top; the ultra-white glass is between the OBA black anti-glare film (AG film) and the blue light board, with a size of 300mm×500mm; the blue light lamp board is at the bottom, with a size of 300mm×500mm, connected with wires to a regulated power supply; and the ultra-white glass and the blue light board lamp beads are in full contact.

[0047] Comparative Example 1

[0048] Take 4 pieces of diffused OCA glue layer black PET anti-glare film (AG film) with a size of 190mm×170mm, 4 pieces of bare crystal light boards with a size of 190mm×170mm, and a 2×4 backlight light box module. Place them in the order of diffused OCA glue layer black PET anti-glare film (AG film), bare crystal light board, and backlight light box module from top to bottom, so that the diffused OCA glue layer black PET anti-glare film (AG film) is attached to the bare crystal light board and after debubbling, the bare crystal light board is inserted in a certain position of the backlight light box module. It should be noted that after the bare crystal light board and the backlight light box module are stably connected, the light board lamp beads are switched to the white state. After connecting the light box to the power supply, turn on the power switch to start the test. The test quantity is 4 pieces and the test time is 240h.

[0049] Comparative Example 2

[0050] Take 4 pieces of transparent OCA adhesive layer transparent PET black anti-glare film (AG film) with a size of 181mm×162mm, 4 pieces of epoxy encapsulated light boards with a size of 181mm×162mm, and a 2×4 backlight light box module. Place them in the order of transparent OCA adhesive layer transparent PET black anti-glare film (AG film), epoxy encapsulated light board, and backlight light box module from top to bottom, so that the transparent OCA adhesive layer transparent PET black anti-glare film (AG film) is attached to the epoxy encapsulated light board and after debubbling, the epoxy encapsulated light board is inserted into a certain position of the backlight light box module. It should be noted that after the epoxy encapsulated light board and the backlight light box module are stably connected, the light board lamp beads are switched to the white state. After connecting the light box to the power supply, turn on the power switch to start the test. The test quantity is 4 pieces and the test time is 240h.

[0051] Example 1

[0052] Take a diffused OCA glue-layer black PET anti-glare film (AG film) with a size of 190mm×170mm, a piece of ultra-white glass with a size of 300mm×500mm and a transmittance greater than 91% that is clean and pollution-free, and a blue light board with a size of 300mm×500mm and a total number of 150 lamp beads that can be lit normally. Place the diffused OCA glue-layer black PET anti-glare film (AG film), ultra-white glass, and blue light aging light board in order from top to bottom, so that the diffused OCA glue-layer black PET anti-glare film (AG film) is attached to the ultra-white glass, and the ultra-white glass is fixed in a certain position on the blue light board. It should be noted that the ultra-white glass is in full contact with the lamp beads of the blue light aging light board. After connecting the light board to the stabilized power supply, connect the circuit and the stabilized power supply, and turn on the stabilized power supply switch to start the test. The test quantity is 2 pieces and the test time is 24 hours.

[0053] Example 2

[0054] Take a transparent OCA adhesive layer transparent PET black anti-glare film (AG film) with a size of 181mm×162mm, a piece of ultra-white glass with a size of 300mm×500mm and a transmittance greater than 91% that is clean and pollution-free, and a blue light board with a size of 300mm×500mm and a total number of 150 lamp beads that can be lit normally. Place them in the order of OBA black anti-glare film (AG film), ultra-white glass, and blue light aging lamp board from top to bottom, and fix the ultra-white glass in a certain position on the blue light board. It should be noted that the ultra-white glass is in contact with all the lamp beads of the blue light aging lamp board. After connecting the lamp board to the regulated power supply, connect the circuit and the regulated power supply, and turn on the regulated power supply switch to start the test. The total power of the lamp board is 150W, the power of a single lamp bead is 1W, the number of tests is 2, and the test time is 24h.

[0055] Comparative Example 1-2 adopts the module light box lighting aging test method commonly used by Mini-LED direct display module manufacturers, and uses spliced ​​light panels to assemble the light box for lighting testing. Example 1-2 adopts the test method provided by the present invention of attaching the OBA black anti-glare film (AG film) to the glass and irradiating it with a blue light panel. The same film material is used in the example and the comparative example. Table 1 shows the results of fading and transmittance changes after aging tests of the example and the comparative example.

[0056] Table 1 Blue light aging test results of Comparative Examples 1, 2 and Examples 1, 2

[0057]

[0058]

[0059] By comparing the experiments of Example 1 and Comparative Example 1 using a diffused OCA glue layer and a black PET anti-glare film (AG film), it can be seen that the test scheme provided by the present invention and the test scheme of Comparative Example 1 can obtain experimental results more quickly, verifying the feasibility of the scheme, and the test results of Example 2 and Comparative Example 2 with a transparent OCA glue layer and a transparent PET black anti-glare film (AG film) are the same. Therefore, the test method provided by the present invention is feasible, and the test accuracy of fading and increased transmittance is high, which is of great help to the evaluation of early product quality.

[0060] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.

Claims

1. A method for testing blue light aging of a film, comprising the following steps: Step (1), sampling: selecting a film to be tested and glass with a light transmittance of more than 90%; Step (2), sample preparation: remove the release film of the film to be tested, attach it to the front surface of the glass, and place the back of the glass on the blue light board to ensure that the glass and the lamp beads of the blue light board are in contact; Step (3), aging test: Turn on the power of the blue light panel and perform an aging test; Step (4), result calculation: After the test is completed, tear off the film to be tested, observe the fading, and calculate the transmittance change value.

2. The testing method according to claim 1, characterized in that: The films to be tested are OBA black anti-glare film (AG film), OBA black adhesive layer anti-glare film (AG film), and OBA white diffusion adhesive (diffusion adhesive).

3. The testing method according to claim 2, characterized in that: The OBA black anti-glare film (AG film) is a kind of film obtained by laminating a diffusion or transparent OCA adhesive layer with a black anti-glare film (AG film).

4. The testing method according to claim 1, characterized in that: The film to be tested is a transparent PET black anti-glare film (AG film) or a body black PET anti-glare film (AG film).

5. The testing method according to claim 1, characterized in that: The transmittance of the OBA black anti-glare film (AG film) without a release film ranges from 20% to 55%.

6. The testing method according to claim 1, characterized in that: The size of the membrane to be tested is O (mm)×P (mm), and the range of O and P is 50-500, or 100, 150, 200, 250, 300, 350, 400.

7. The testing method according to claim 1, characterized in that: The glass is ultra-white glass.

8. The testing method according to claim 1, characterized in that: The ultra-white glass is ultra-transparent low-iron glass with a light transmittance of more than 91%, or 95% or 98%.

9. The testing method according to claim 1, characterized in that: The glass has a thickness of 2-10 mm, or 4 mm, 6 mm, 8 mm, and a smooth surface.

10. The testing method according to claim 1, characterized in that: The size of the glass is M (mm)×N (mm), and the range of M and N is 100-800, or 200, 300, 400, 500, 600, 700.

11. The testing method according to claim 1, characterized in that: The lamp board is a blue light bead lamp board with a size of M (mm) × N (mm), and the range of M and N is 100-800, or 200, 300, 400, 500, 600, 700.

12. The testing method according to claim 1, characterized in that: The number of lamp beads in the blue light lamp bead lamp board is 100-200, or 120, 150, or 180.

13. The testing method according to claim 1, characterized in that: The OBA black anti-glare film (AG film) and the glass are in a pressure-free rolling attachment state.

14. The testing method according to claim 1, characterized in that: During the aging test, the blue light aging process requires regular adjustment of the voltage and current of the voltage-stabilized power supply to maintain a total power of 100-200W, or 120W, 150W, 160W, 180W, and a single lamp bead power of 0.5W-3W, or 1W, 1.5W, 2.0W, 2.5W.

15. The testing method according to claim 1, characterized in that: The aging test time is 10-30h, or 15h, 20h, 24h, 26h, 28h.

16. The testing method according to claim 1, characterized in that: The transmittance is tested by a transmittance haze meter.

Citation Information

Patent Citations

  • Liquid crystal light adjusting film's logical electrical ageing check out test set

    CN207133541U

  • Power-on aging detection equipment for liquid crystal dimming film

    CN214954408U